The nexus of safe asset shortage, credit growth, and financial instability - Sujin Kim (Asian Development Bank Institute (ADBI), 2020)
Does a shortage of safe assets sow the seeds of instability in a financial system? This paper empirically explores the hypothesis of safe asset shortage-induced excess credit booms and financial instability. As an alternative step forward from the assumption of growth- or wealth-based demands for safe assets, the study underlines demographic factors as a key determinant of safe asset demands. Based on the long-run trends of aging and government debt, I construct a new safe asset shortage index. Using the index, consecutive empirical exercises confirm the positive relationship of safe asset shortage-credit expansion-aggregate risks of a financial system. The estimation of the crisis probabilistic model for 17 advanced economies in 1960-2013 presents new evidence that the (high) level of private credit at a time of increasing safe asset shortage is the major predictor of financial crises. The fixed-effect panel analysis results for 18 advanced countries in 1980-2016 also show a significant, positive contribution of a safe asset shortage to credit growth. The total effect of the shortage depends positively on securitization growth and negatively on net capital outflows. The latter effect is considerably dominant.
Keywords: E21; E62; G00; G01; J10; 330; safe asset shortage index; demographics; credit; financial crises; financial stability; government debts; capital flows